A decision-making framework for precision marketing. Issue 7 (1st May 2015) - You, Zhen; Si, Yain-Whar; Zhang, Defu; Zeng, XiangXiang; Leung, Stephen C.H.; Li, Tao
Highlights A decision-making framework for precision marking based on data-mining techniques. A trend model to accurately predict monthly supply quantity. A RFM (Recency, Frequency and Monetary) model to select customer attributes. Decision trees and Pareto values are combined for grouping customers. A real case-study to demonstrate the effectiveness of the proposed framework.